Determination Of The Selling Price Of Dimsum Products Through Target Costing Setting - Pujiastuti, Heni; Djamin, Arydian B. (Adpebi Science Series, 2022)
This article provides an overview of the development of the ready-to-eat food business which is a trend in 2022 by considering production factors, raw material factors, quality and efficient costs, then premium products are produced with price advantages and special tastes. The production process begins with product design to the production stage which involves several departments with quality control that is strict enough to produce quality and hygienic products. Target costing is the most important part of a production process, in addition to being related to the calculation of production costs, it is also a controlling tool as well as a determinant of suppliers to get quality products at competitive costs. The purpose of this study is to analyze the cost of controlled production through the application of Target Costing and the determination of managerial policies related to the efficiency of the production process. The method of data collection and processing in this study was carried out by observation, interviews, and literature studies. The results of the study illustrate that through the application of Target Costing, the company is able to carry out various efficiencies including raw material efficiency through selected suppliers. Labor efficiency with the right time standards and determination of factory overhead is treaceble to the products produced. It is hoped that this research will provide theoretical benefits that contribute to the science of Management Accounting related to the calculation of standard costing and performance improvement. Meanwhile, the practical benefits are in considering a special order policy for many products.